2020
DOI: 10.1007/s00417-020-04907-1
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal evaluation in patients under alpha-lytic therapy

Abstract: Purpose To detect any choroidal thickness (CT) change in patients after alpha-lytic drugs withdrawal that could help in the cataract surgery timing decision. Methods Twenty-five eyes of 25 patients (mean age: 76 ± 7 years) under alpha-lytic therapy, and 25 eyes of 25 control subjects (CS) (mean age: 75 ± 7 years) without alpha-lytic therapy, both scheduled for cataract surgery in the fellow eye, were included in this observational, prospective, non-randomized study. All patients underwent EDI-OCT during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
(18 reference statements)
0
24
0
Order By: Relevance
“…CVI is a recent imaging tool that allows a more accurate evaluation of the choroidal structure, facilitating discrimination of the vascular and stromal components, and also providing their quantification 14 , 15 . This new parameter has already been used to evaluate different ocular and systemic disorders and pathological conditions 25 28 . To the best of our knowledge, this is the first study which utilizes CVI in the choroid appraisal and analysis of patients with celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…CVI is a recent imaging tool that allows a more accurate evaluation of the choroidal structure, facilitating discrimination of the vascular and stromal components, and also providing their quantification 14 , 15 . This new parameter has already been used to evaluate different ocular and systemic disorders and pathological conditions 25 28 . To the best of our knowledge, this is the first study which utilizes CVI in the choroid appraisal and analysis of patients with celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…13 In chronic α antagonist users, CT is significantly decreased from baseline after abstaining from α antagonist use for 1 month. 14 However, a randomized trial showed that neither oral alfuzosin nor oral tamsulosin were associated with significant change in CT from baseline at 1 and 3 months of use. 15 Vasodilation secondary to sympathetic adrenoceptors in the choroid 13 and affinity for tamsulosin for melanin in the choroid 90 were hypothesized causes for CT.…”
Section: Alpha-1 Adrenoceptor Antagonistsmentioning
confidence: 99%
“…In the last few years, choroidal evaluation has been widely used in several conditions. 2 In this particular paper, the authors utilised the choroidal vascularity index (CVI), which represents the ratio between the vascular luminal and total choroidal areas. This index was first described by Agrawal to better distinguish the luminal from the stromal area.…”
mentioning
confidence: 99%